Keeping an Eye on the Refutation Effect: The Role of Prior Knowledge and Text-Based Interest on Attention Allocation. Issue 10 (26th November 2022) - Catrysse, Leen; Chauliac, Margot; Donche, Vincent; Gijbels, David
ABSTRACT: This study examined the relationship between refutation texts and attention allocation by focusing on the interaction between important reader-and-text characteristics. Specifically, the authors investigated how prior knowledge and text-based interest affect attention allocation on refutation/control statements, topic, and explanatory and concluding sentences in refutation and nonrefutation texts. We employed eye tracking to monitor the reading behavior of 92 students in higher education. The results revealed that during first-pass regressive reading, nonrefutation-text readers, compared with refutation-text readers, read topic sentences longer, indicating the correct scientific information. Concluding sentences, summarizing the correct scientific information, were reread for longer by refutation-text readers. With increasing prior knowledge, refutation texts were read more slowly than nonrefutation texts during first-pass reading. A higher text-based interest increased rereading time in the refutation text and decreased rereading time in the nonrefutation text. This study advances present knowledge in the field by demonstrating that the interaction between text and reader characteristics affects attention allocation in reading and comprehension.